DAMPAK TUNTUTAN COMFORT WOMEN TERHADAP HUBUNGAN DIPLOMATIK JEPANG – KOREA SELATAN - Sitorus, Erlin Luz Clarita Br; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the impact of the comfort women issue on diplomatic relations between South Korea and Japan. This research employs a qualitative approach using a case study method and is analyzed through the lens of historical constructivism developed by Duncan Bell, alongside Charles Tilly's theory of social movements. The study focuses on the period from 2015 to 2022, covering the dynamics following the 2015 Comfort Women Agreement. The findings indicate that the collective memory of the comfort women issue plays a critical role in fueling public resistance against Japan, as evidenced by social movements, boycotts of Japanese products, and domestic pressure on the South Korean government to reassess diplomatic and security cooperation. This study concludes that resolving the comfort women issue requires more than a legal-formal approach; it demands an empathetic and symbolic response that addresses the historical and moral dimensions of the problem. Keywords: Comfort Women, The Korean Council, South Korea, Japan, 2015 Agreement, Diplomatic Tensions